Professional development and literacy coaching: a case study of kindergarten, first, and second grade balanced literacy instruction - DeWeese, Christy Suzanne Puckett (Kansas State University, 2008)
To become lifelong readers, young children require instruction from teachers who integrate their knowledge of the reading process and expert instructional skills to support students' progress in reading and writing. These teachers are entitled to support from professional development to assist their implementing instructional approaches, which lead to student achievement. The purpose of this qualitative case study is to describe the impact of a year long balanced literacy professional development on 13 K-2 teachers and their students. The study focuses on the potential impact of ongoing professional development and literacy coaching. Participants engaged in study sessions to expand their understanding of literacy learning processes, to read recent reading research, and to implement guided reading instruction. Three of the participants allowed me to act as their literacy coach in their K-2 classrooms. Results of this study suggest that participating teachers made changes in instructional practices, which aligned with balanced literacy practices. The three teachers who worked with me as their literacy coach expressed positive impacts from the opportunities to collaborate in their classrooms with a coach. Results of the study reflect differences in teachers' responses to professional development and to literacy coaching. Even with trusting relationships, not all teachers became reflective or analytical. The findings of this study confirm and support the literature and research that show the literacy goals of all children can be met through a balanced literacy approach to instruction which is designed and guided by focused and sustained professional development to deepen teachers' understandings.
Keywords: Professional development; Literacy coaching; Balanced literacy; Education, Elementary (0524)